2020
DOI: 10.1002/ijc.33190
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of erythrocyte polyunsaturated fatty acids and risk of colorectal serrated polyps and conventional adenomas

Abstract: The influence of polyunsaturated fatty acids (PUFAs) on risk of colorectal cancer precursors remains largely unknown. We examined the associations of erythrocyte PUFAs, including n−3 and n−6 PUFAs, with risk of colorectal conventional adenomas and serrated polyps in 4517 participants from three US prospective cohorts who had provided a blood sample and undergone at least one endoscopic examination. We calculated the multivariable odds ratios (ORs) per 1 SD increment in individual PUFAs and the ratio of n−6/n−3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
(111 reference statements)
0
8
0
Order By: Relevance
“…This large US study (n=1 41 143 with follow-up for 18–20 years) found that increased intake of marine O3FAs was associated with lower risk of both CA (p<0.001) and SP (p=0.004) 21. However, a smaller study inside the same prospective cohort did not observe any relationship between red blood cell (RBC) O3FA (as the % total fatty acids) and risk of either CA (n=493, median RBC EPA level 0.44%) or SP (n=316, median RBC EPA 0.43%) 22…”
Section: Primary Prevention: Colorectal Polyp Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…This large US study (n=1 41 143 with follow-up for 18–20 years) found that increased intake of marine O3FAs was associated with lower risk of both CA (p<0.001) and SP (p=0.004) 21. However, a smaller study inside the same prospective cohort did not observe any relationship between red blood cell (RBC) O3FA (as the % total fatty acids) and risk of either CA (n=493, median RBC EPA level 0.44%) or SP (n=316, median RBC EPA 0.43%) 22…”
Section: Primary Prevention: Colorectal Polyp Studiesmentioning
confidence: 92%
“…The difference in EPA content (as % total fatty acids) between these studies highlights heterogeneity in study populations that makes interpretation of the relationship between tissue O3FA levels and neoplastic risk challenging, even when detailed dietary data are available (table 1). 22 25 26…”
Section: Primary Prevention: Colorectal Polyp Studiesmentioning
confidence: 99%
“…Eleven cohorts of dietary intake of ALA were included, involving 10,583 cases and 854,818 participants in 9 prospective cohort studies ( 10 , 30 , 31 , 33 36 , 38 , 39 ) and 2 case-cohort studies ( 32 , 37 ), and dietary measurements were evaluated by food frequency questionnaires. For biomarkers of ALA, 5 prospective studies were included, involving 2,051 cases and 48,421 participants in 2 studies based on plasma ( 17 , 37 ), 2 on erythrocyte ( 18 , 40 ), and 1 on AT ( 16 ). ALA levels in different biospecimens were quantified by gas-liquid chromatography (GLC) and the measurement unit was set as a percentage, except for one study (μmol/L) ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both male and female were reported in five articles ( 17 , 32 , 37 , 39 , 40 ), only male in two articles ( 10 , 30 ), only female in four articles ( 18 , 31 , 34 , 38 ), and 4 articles separately reported male and female ( 16 , 33 , 35 , 36 ). As for CRC locations, 13 articles reported total CRC ( 10 , 16 18 , 30 , 31 , 33 39 ), whereas 2 articles only separately reported colon cancer and rectal cancer ( 32 , 40 ). Among all of the included studies, quality scores assessed by the 9-star NOS ranged from 7 to 9, with a median quality (≤7 stars) in 2 studies ( 36 , 39 ) and high quality (≥ 8 stars) in 13 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation